Using the technique of air injection into soil to determine penetration resistance force at different humidity - Imad Rezakalla Antypas; Alexey G. Dyachenko (Advanced Engineering Research, 2016)
The work objective is to establish the relationship of such soil parameters as soil moisture (SM), penetration resistance force (PRF), and time of the compressed air release. During the investigation, the following tasks are solved: identifying the impact of humidity on the air permeability of various types of soil; establishing the relationship between the soil PRF and the air permeability of the soil types under study; gain in experience of using a penetrometer for measuring the penetration resistance force of different types of soils. The connectivity between humidity and soil penetration resistance force is proved. At that, the highest correlation coefficient is observed in limestone, and the lowest - in alumina and sandy loam. The relationship between the content of pores filled with air, and the air permeability of the soil is determined. The number of pores filled with air ( ) increases with the decreasing of the number of pores filled with water. Whereas the compressed air release time ( ) decreases over the natural logarithm amplitude: